Graphite carbon nitride/boron-doped graphene hybrid for efficient hydrogen generation reaction. (19th June 2018) - Yang, Liang; Wang, Xin; Wang, Juan; Cui, Guomin; Liu, Daoping
Abstract: Metal-free carbon materials, with tuned surface chemical and electronic properties, hold great potential for the hydrogen evolution reaction (HER). We designed and synthesized a CN/BG hybrid electrocatalytic system with a porous and active graphite carbon nitride (CN) layer on boron-doped graphene (BG). A porous CN layer on graphene could provide exposed defects and edges that act as active sites for proton adsorption and reduction. The composition, structure, surface electronics, and chemical properties of this CN/BG hybrid system were tuned to obtain excellent HER activity and stability. Detailed surface chemical, morphological, and structural analyses demonstrated the synergetic effect arising from the electronic interaction between CN and BG, which contributed to the enhanced electrocatalytic performances.